2019
DOI: 10.1007/s00428-019-02672-z
|View full text |Cite
|
Sign up to set email alerts
|

Cause of death and significant disease found at autopsy

Abstract: The use of clinical autopsy has been in decline for many years throughout healthcare systems of developed countries despite studies showing substantial discrepancies between autopsy results and pre-mortal clinical diagnoses. We conducted a study to evaluate over time the use and results of clinical autopsies in Sweden. We reviewed the autopsy reports and autopsy referrals of 2410 adult (age > 17) deceased patients referred to two University hospitals in Sweden during two plus two years, a decade apart. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
2
30
1
1
Order By: Relevance
“…Regarding the demographic data of the deceased patients, a significantly higher number of male patients underwent a postmortem examination. These findings are consistent with previous publications [ 3 ]. According to Cameron et al, the reason for higher autopsy rates in male patients is the higher likelihood of female relatives to give the permission for a postmortem examination [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Regarding the demographic data of the deceased patients, a significantly higher number of male patients underwent a postmortem examination. These findings are consistent with previous publications [ 3 ]. According to Cameron et al, the reason for higher autopsy rates in male patients is the higher likelihood of female relatives to give the permission for a postmortem examination [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…In Germany, a decline in overall numbers of autopsies of 30% between 2005 and 2014 was detected [ 1 ]. This number is concordant with previous reports from other countries such as France, Sweden, and the USA where the decline has been reported to be even more severe [ 2 , 3 ]. A survey among pathologists in Germany revealed an autopsy rate of patients who died in a hospital of 3.63% in 2013 and 3.39% in 2014 [ 4 ].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…S obzirom na to da je veliki broj pacijenata imao hroničnu ishemijsku bolest srca, ovakav rezultat se mogao očekivati. Naš rezultat je sličan rezultatima drugih autora [1,5,6]. Međutim, u slučajevima kada se radi o naprasnoj smrti, učestalost srčanih uzroka smrti je veća od 50% [7,8].…”
Section: Diskusijaunclassified
“…The current study showed declining autopsy rates over the years. Several causes for the decline have been identified, the most important being few physicians requesting for autopsy nowadays,26 difficulty in obtaining consent from relatives of deceased patients,27 and use of radiological imaging techniques as substitution for autopsy 28,29. Theoretically, this could result in selection bias, because of a more predominant selection of patients with an unexpected death or without a clear cause of death.…”
mentioning
confidence: 99%